Preparation, mechanical, and thermal properties of CrNbO4: A novel dual-functional scale to protect RHEAs from oxidation and thermal attack - Shuang Zhang; Jian Zhang; Xiaohui Wang; Huimin Xiang; Cheng Fang; Wei Xie; Yanchun Zhou (Journal of Advanced Ceramics)
Cr–Nb-containing refractory high-entropy alloys (RHEAs) have high strength above 1200 °C but low density close to that of Ti-based alloys, which makes them promising for application in aero engines. However, oxidation is the bottleneck that limits their practical application. Recently, CrNbO4 has been found to effectively protect them from oxidation. Nevertheless, little is known about this oxide. To elucidate the protection mechanism of CrNbO4 and explore its properties, we report for the first time the microstructure, mechanical, and thermal properties of CrNbO4. Using atomic-resolution high-annular dark field (HAADF) and annular bright field (ABF) techniques, we confirmed the rutile-type structure of CrNbO4, identified the precipitation of Cr2O3, and observed Cr segregation at the interface boundary between CrNbO4 and Cr2O3. The Young’s modulus (E), shear modulus (G), and bulk modulus (B) of CrNbO4 are 253, 100, and 180 GPa, respectively, whereas the Vickers hardness (HV), flexural strength (σf), and fracture toughness (KIC) of CrNbO4 are 10.2±0.58 GPa, 205±8 MPa, and 1.54±0.12 MPa·m1/2, respectively. The measured melting point of CrNbO4 is 2053±20 K. The anisotropic thermal expansion coefficient (TEC) is αa = (5.38±0.09)×10−6 K−1, αc = (7.44±0.14)×10−6 K−1, and the average TEC is (6.07±0.12)×10−6 K−1, which is close to that of refractory metals and RHEAs. Interestingly, the room temperature thermal conductivity of CrNbO4 is 1.09 W·m−1·K−1 and decreases to 0.45 W·m−1·K−1 at 1473 K, which is lower than that of most of the currently well-known thermal insulation materials. Consequently, CrNbO4 can be considered a novel dual-functional scale on top of RHEAs to protect them from oxidation and thermal attack.